Energy and orientation of Bloch type domain walls in magnatics with mixed anisotropy - Granovskii, Ya.I.; Leonov, A.A.; Mamalui, Yu.A.; Siryuk, Yu.A. (Functional Materials, 2006)
Theoretical energy calculation has been carried out for domain walls (DW) of several types with different gyration angles of the magnetization vector in ferrite-garnet crystals with mixed anisotropy (presence of the uniaxial EK and cubic anisotropy EK). The DW orientations satisfying to the energy minimum have been determined. It is shown that at parameter v = KU/K₁, the 1-st type DW (the magnetization vector in the neighboring domains have the same positive projection onto the axis [111], the normal to the film surface) are transformed into the 2-nd type DW (the projections of opposite signs, the angle between magnetization vectors being distinct from 180°).